How to make money in the translation business. (9th February 2016) - DALE, ROBERT
Abstract: Machine Translation research suffered a major blow in the 1960s, but it came back with a vengeance. From a commercial point of view, it's now a mature technology that many Internet users take for granted. We look at where we are now, and consider the scope for new entrants into the market.